Analysis Of Milk From Different Sources Based On Light Propagation And Random Laser Properties - Nur Ain Insyirah Muhamad Kamil; Wan Zakiah Wan Ismail; Irneza Ismail; Juliza Jamaludin; Nur Syaida Hanasil; Raja Kamarulzaman Raja Ibrahim (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Indexed by WOS/SCOPUS